Risk Factors for 30-Day Readmission following Knee Arthroscopy - Hartwell, Matthew J.; Morgan, Allison M.; Johnson, Daniel J.; Nicolay, Richard W.; Christian, Robert A.; Selley, Ryan S.; Terry, Michael A.; Tjong, Vehniah K. (The Journal of Knee Surgery, 2019)
This study evaluates knee arthroscopy cases in a national surgical database to identify risk factors associated with readmission. The American College of Surgeons National Surgical Quality Improvement Program database was queried from 2012 to 2016 for billing codes related to knee arthroscopy. International Classification of Diseases diagnostic codes were then used to exclude cases which involved infection. Patients were subsequently reviewed for readmission within 30 days. Univariate and multivariate analyses were then performed to identify risk factors associated with 30-day readmission. A total of 69,022 patients underwent knee arthroscopy. The overall 30-day complication rate was 1.75% and the 30-day readmission rate was 0.92%. On multivariate analysis, age > 60 years (odds ratio [OR], 1.29; 95% confidence interval [CI], 1.07–1.55), smoking (OR, 1.40; 95% CI, 1.15–1.70), recent weight loss (OR, 13.22; 95% CI, 5.03–34.73), chronic obstructive pulmonary disease (OR, 1.98; 95% CI, 1.39–2.82), hypertension (OR, 1.48; 95% CI, 1.23–1.78), diabetes (OR, 1.92; 95% CI, 1.40–2.64), renal failure (OR, 10.65; 95% CI, 2.90–39.07), steroid use within 30 days prior to the procedure (OR, 1.91; 95% CI, 1.24–2.94), American Society of Anesthesiologists (ASA) class ≥ 3 (OR, 1.69; 95% CI, 1.40–2.04), and operative time > 45 minutes (OR, 1.68; 95% CI, 1.42–2.00) were identified as independent risk factors for readmission. These findings confirm that the 30-day overall complication (1.75%) and readmission rates (0.92%) are low for knee arthroscopy procedures; however, age > 60 years, smoking status, recent weight loss, chronic obstructive pulmonary disease, hypertension, diabetes, chronic steroid use, ASA class ≥ 3, and operative time > 45 minutes are independent risk factors for readmission.
Keywords: knee arthroscopy; risk factors for readmission; 30-day readmission